Indicators of mental health services evaluation process - Ana Caroline Gonçalves Cavalcante; Elizabeth Esperidião; Nathália Santos Silva; Kellykan Silva Silva; Adrielle Cristina Silva Souza (Universidade Federal de Goias, 2014)
This descriptive, exploratory and qualitative study was performed with the objective to evaluate the structure of the Mental Health Service Network of the Municipal Health Department of Goiania, the capital city of Goias state, Brazil. Data were collected using a semi-structured instrument and photographic records, and analyzed using Atlas.ti 6.2, and based on Donabedian's theoretical framework. Various conditions were observed for service facilities; from structures that were precarious and unsuitable for therapy, to facilities that were welcoming and had good accessibility. The main positive aspect was the diversity of multidisciplinary teams. Making service facilities appropriate is imperative, although it is recognized that the municipality is currently undergoing reformulation, aiming at meeting the needs of the National Policy for Mental Health. Furthermore, intersectoral partnerships should be established for evaluation processes, particularly in the academia and service domains, which could generate the desired impact on health care to clients of specialized services. Descriptors: Health Services Evaluation; Mental Health; Structure of Services.